Sentencing: New Trajectories in Law - Freer, Elaine (New Trajectories in Law, 2021)
Introduction 1. Sentencing as Punishment 2. Sentencing to Reduce Crime, and as Deterrence 3. Sentencing as Rehabilitation 4. Sentencing as Protection 5. Sentencing as Reparation Concluding Thoughts